2006
DOI: 10.1111/j.1468-3083.2006.01573.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acitretin on spermatogenesis of rats

Abstract: In this experimental study the possible effects of the acitretin on the spermatogenesis of the rats were investigated histopathologically. Thirty-nine male adult Wistar albino rats were divided into 3 groups as two experimental groups and one control group. The first group consisting 14 rats were applied orally standard dose (0.75 mg/kg/day) acitretin and the second group consisting 16 rats were applied high dose (1.5 mg/kg/day) acitretin. Acitretin was given within dimetil sulphoxide (DMSO), which was diluted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The guidelines in many countries recommended not using acitretin in women who are pregnant or who are considering becoming pregnant during therapy or for at least 2–3 years after discontinuation . Nevertheless, the standard (0.75 mg/kg per day) and high (1.5 mg/kg per day) doses of acitretin have not been shown to be associated with abnormalities in spermatogenesis of rats, similar to that reported in psoriatic patients…”
Section: Discussionmentioning
confidence: 65%
“…The guidelines in many countries recommended not using acitretin in women who are pregnant or who are considering becoming pregnant during therapy or for at least 2–3 years after discontinuation . Nevertheless, the standard (0.75 mg/kg per day) and high (1.5 mg/kg per day) doses of acitretin have not been shown to be associated with abnormalities in spermatogenesis of rats, similar to that reported in psoriatic patients…”
Section: Discussionmentioning
confidence: 65%
“…A study of male lizards treated with all‐trans‐retinoic acid showed that retinoic acid severely depleted seminiferous epithelium and, therefore, had a significant effect on spermatogenesis . In contrast, a study showed that standard and high doses of acitretin did not affect spermatogenesis of rats . Furthermore, one review reported that in preclinical data, including genotoxicity assays and a male rat reproduction toxicology study, acitretin did not affect reproductive outcome in females mated with males given acitretin .…”
Section: Resultsmentioning
confidence: 99%
“…Lizard study showed depleted seminiferous epithelium with all-trans-retinoic acid (47). Rat study showed no direct sperm effect (48).…”
Section: Retinoid Agents Acitretinmentioning
confidence: 93%
“…In accordance to results of this study, in a study conducted on rats, the authors suggested that neonatal retinoid exposure may have affected sexual parameters due to the binding of nuclear steroid receptors [31] . In contrast, Sengör and his colleagues [32] had found no effect of different doses of acitretin on spermatogenesis; but this study was done on rats.…”
Section: Discussionmentioning
confidence: 68%